PERILAKU SUBJEK DALAM BAHASA KEMAK KABUPATEN BELU NUSA TENGGARA TIMUR - I Wayan Budiarta (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to identify subject characteristics of the Kemak language in Belu Regency, East Nusa Tenggara. The subject characteristics are identified by testing thearguments predicted as a subject. The data were spoken and written data in the form ofclauses or sentences collected through the field linguistic method, using direct elicitationsupported by interviews. The selected informants were native speakers. The findings showthat the subject in the Kemak language has the following characteristics. (1) The subjectappears in the pre-verbal position in the canonical structure. (2) An adverb and a negationmarker can be inserted between the subject as a pre-verbal argument and the predicate.(3) The subject can be relativized. (4) A floating quantifier can be inserted between subjectand predicate. (5) The subject can be made reflexive. (6) Non-subject arguments (directand indirect objects) can be raised to be a subject through the raising mechanism. (7) Thesubject can be focused through the presence of the focus marker te ‘that’ which appearsdirectly after the subject. (8) The subject can be controlled.